THE ACQUISITION OF TÉH AND MAH BY THE L2 LEARNERS OF SUNDANESE - Eri Kurniawan (Faculty of Languages and Arts, Universitas Negeri Yogyakarta, 2013)
This study examines the second language acquisition of the pragmatic particles téh and mahin L2 Sundanese by Indonesian native speakers. Two groups were compared: (i) a native control group and (ii) an advanced group of Indonesian-speaking adult L2 learners of Sundanese. A pragmatic context-matching felicitousness judgment task wasemployed, following Rothman (2009). A descriptive analysis and a quantitative analysis of the results were conducted, which specifically compared the performance mean score of the L2 learners to that of the native control group. A t-test was used with the alpha setat (0.05) for a 95% confidence level. Assuming the Interface Hypothesis (TsimpliSorace, 2006; Valenzuela, 2006; Sorace, 2007, inter alia), the study presents evidence contrary to the claim that properties mediated at the syntax-pragmatic interface are more difficult to acquire than purely syntactic properties. The advanced L2 learners of Sundanesedemonstrate the native-like L2 knowledge of téh and mah.